Rancang Bangun Sistem Pemantauan dan Pengendali Kualitas Udara Pada Aplikasi Welding Habitat Proses Welding Pipeline Sistem Dengan Data Logger - Ahmad Daerobi; Abdul Multi; Masbah R.T. Siregar (Institut Sains dan Teknologi Nasional, 2023)
Abstract Air Quality Monitoring and Control System is a method of monitoring and controlling air quality in an area or place where air contamination may occur in an activity or work. In this case, the Air Quality Monitoring and Control System is applied to the welding habitat or the welding house in the system pipe welding process. At this time, the welding habitat in the welding pipe pipeline system with the shielding gas process has not been monitored and controlled for air quality during the welding process, this condition causes the welder in the welding habitat to become uncomfortable which can affect the quality of the welding and endanger the welder's health. For this reason, an air quality monitoring and control system is needed that can unite and control the air quality in the welding habitat during the welding process. The purpose of the design of this Air Quality Monitoring and Control System is to make the welding process in the welding habitat of the system pipe welding process more comfortable and safer for the welder's health. So that the welder can concentrate fully on the welding process and produce good and quality welding production. With the application of this system, it can provide a level of weld repair that can reduce welding repair costs incurred by the Company. Keywords: Air Quality; Data Logger; ESP32; ISPU (Air Pollution Standards Index); Sensors